Isolation and characterization of algicidal bacteria from freshwater aquatic environments in China - Ren, Sanguo; Jin, Yuanpei; Ma, Jianan; Zheng, Ningning; Zhang, Jie; Peng, Xingyu; Xie, Bo (Frontiers in Microbiology, 2023)
Algicidal bacteria can inhibit the growth of algae or lyse algal cells, thus playing roles in shaping aquatic microbial communities and maintaining the functions of aquatic ecosystems. Nevertheless, our understanding of their diversities and distributions remains limited. In this study, we collected water samples from 17 freshwater sites in 14 cities in China and screened a total of 77 algicidal bacterial strains using several prokaryotic cyanobacteria and eukaryotic algae as target strains. According to their target-specificities, these strains were classified into three subgroups, prokaryotic cyanobacterial algicidal bacteria, eukaryotic algal algicidal bacteria, and broad-target algicidal bacteria, each displaying distinctive compositions and geographical distribution patterns. They are assigned to Proteobacteria, Firmicutes, Actinobacteria, and Bacteroidetes bacterial phyla, of which Pseudomonas and Bacillus are the most abundant gram-negative and gram-positive genus, respectively. A number of bacterial strains, such as Inhella inkyongensis and Massilia eburnean, are potentially newly reported algicidal bacteria. The diverse taxonomies of these bacteria, their algal-inhibiting abilities, and their distributions have suggested that there are rich algicidal bacterial resources in these aquatic environments. Our results may provide new microbial resources for algal-bacterial interaction studies, and shed new insights into how algicidal bacteria can be used for the control of harmful algal blooms, as well as in algal biotechnology.